Shoulder and elbow injuries in NCAA football players, 2009-2010 through 2013-2014 - Goodman, A. D.; Raducha, J. E.; DeFroda, S. F.; Gil, J. A.; Owens, B. D. (The Physician and Sportsmedicine, 2019)
Background: Although football is one of the most popular collegiate sports, the epidemiology of and risk factors for shoulder and elbow injuries in this population not been recently described. We aimed to characterize this incidence in National Collegiate Athletic Association (NCAA) football players, determine risk factors, and establish outcomes after injury. Methods: All shoulder and elbow injuries in men`s football occurring during the 2009-2010 through 2013-2014 academic years were retrospectively identified in the NCAA Injury Surveillance Program database. The injury incidence per 10,000 athletic exposures (AEs) was calculated overall, and by different risk factors. In addition to descriptive statistics, risk factors were compared using injury risk-ratios, and outcomes were compared using injury proportion ratios. Results: NCAA football players sustained 1,187 shoulder and elbow injuries in 899,225 AEs (incidence: 13.20/10,000 AE), most commonly acromioclavicular separation (29.9%), anterior shoulder subluxation (9.0%), shoulder contusion (9.0%), and rotator cuff tear/sprain (8.0%). Together, shoulder instability comprised 28.1% of injuries. Injuries were split evenly between offense (43.5%) and defense (45.9%), and a tackling mechanism caused 37.7%, with 30.3% coming from blocking. The incidence was eight times higher in competition than practice (62.9/10,000 vs 7.9/10,000AE, p < 0.001). Surgery was performed for 9.9% of injuries, and most commonly for all types of shoulder instability (56.8% of surgeries). Injuries were season-ending in 5.2% of players. The likelihood of an injury being season-ending was 2.9 times greater for recurrent injuries than a new injury (p < 0.001); 86.1% of all injuries were new. Conclusions: Shoulder and elbow injuries to NCAA football players can be severe. Competition had an eight times higher incidence than did practice. Tackling and blocking were the most common mechanisms, while AC separation and shoulder instability were the most common injuries. This epidemiology may help players, coaches, trainers, and governing bodies target injury-prevention programs and assess improvement over time.